2020
DOI: 10.3389/fnins.2020.00777
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Profiling of Oxylipins in Acute Experimental Intracerebral Hemorrhage

Abstract: Oxylipins are a series of bioactive lipid metabolites derived from polyunsaturated fatty acids that are involved in cerebral homeostasis and the development of intracerebral hemorrhage (ICH). However, comprehensive quantification of the oxylipin profile in ICH remains unknown. Therefore, an ICH mouse model was constructed and liquid chromatography tandem mass spectrometry was then performed to quantify the change in oxylipins in ICH. The expression of the oxylipin relative enzymes was also reanalyzed based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In contrast, lipid metabolism was significantly affected in the young mice. Oxylipin profiling at 12 h, 24 h, and 72 h after ICH in adult mouse brains was explored in a recent study, and the number of changed oxylipins was the highest on the first day of ICH [ 10 ]. In the present study, the expression of the apolipoprotein A-I (Apoa1) protein differed between young and aged ICH model mice, being significantly elevated exclusively in young mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, lipid metabolism was significantly affected in the young mice. Oxylipin profiling at 12 h, 24 h, and 72 h after ICH in adult mouse brains was explored in a recent study, and the number of changed oxylipins was the highest on the first day of ICH [ 10 ]. In the present study, the expression of the apolipoprotein A-I (Apoa1) protein differed between young and aged ICH model mice, being significantly elevated exclusively in young mice.…”
Section: Discussionmentioning
confidence: 99%
“…A proteomics analysis detected differentially expressed proteins (DEPs) in plasma among young, middle-aged, and older healthy individuals and confirmed that insulin-like growth factor 1 is a promising novel approach for ameliorating aging-associated acute brain injury after ICH [ 9 ]. The other transcriptomic analysis distinguished the expression pattern of oxylipin enzymes between middle-aged and aged rats 3 days after experimental ICH induction and revealed that among the specific differentially expressed genes (DEGs), Cyp1a1 and Cyp2e1 were the most significant DEGs in the two age groups [ 10 ]. In addition, in pathological findings of animals with ICH, more severe brain swelling was observed in aged animals than in young animals, and aged animals exhibited different glial responses from young animals, impaired lesion resolution, and neuronal death [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GSE24265 Series Matrix File was downloaded from the GEO public database, noted by the GPL570 annotation file, of which the expression profile data belonged to 11 samples, including the perihematomal areas, gray matters, and white matters of 7 patients in the healthy control group and 4 patients with ICH ( Rosell et al, 2011 ). The GSE149317 Series Matrix File (only used to verify the expression level of key genes) was downloaded from the GEO public database, and the annotated File is GPL24688 ( Yuan et al, 2020 ). The microarray data included 6 cases in the healthy control group and 6 patients in the ICH group.…”
Section: Methodsmentioning
confidence: 99%
“…Browsing, searching, and filtering data, information and digital content (1) Interacting through digital technologies (4) Developing digital content (10) Protecting devices (14) Solving technological problems (18) Evaluating data, information and digital content (2) Sharing through digital technologies (5) Integrating and reelaborating digital content (11) Protecting personal data and privacy (15) Identifying needs and technological responses (19) Managing data, information and digital content (3) Engaging in citizenship through digital technologies (6) Copyright and licenses (12) Protecting health and well-being (16) Creatively using digital technologies (20) Collaborating through digital technologies (7) Programming (13) Protecting the environment (17) Identifying digital competence gaps (21) Netiquette (8) Managing digital identity (9) *Specific knowledge, skills and attitudes are numbered to show the results in Table 11.…”
Section: Safety Problem Solvingmentioning
confidence: 99%